2017
DOI: 10.3390/land6020028
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Land Fragmentation at Urban Fringes: An Application of Urban-To-Rural Gradient Analysis in Adelaide

Abstract: Abstract:One of the major consequences of expansive urban growth is the degradation and loss of productive agricultural land and agroecosystem functions. Four landscape metrics-Percentage of Land (PLAND), Mean Parcel Size (MPS), Parcel Density (PD), and Modified Simpson's Diversity Index (MSDI)-were calculated for 1 km × 1 km cells along three 50 km-long transects that extend out from the Adelaide CBD, in order to analyze variations in landscape structures. Each transect has different land uses beyond the buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…Land cover distributions are driven by complex environmental, social and economic conditions that are focal points for sustainable land cover plans [56,57]. The distributions frequently change due to human activities that have been increasingly influenced by political plans during the last few centuries, for instance urbanization or intensively using agricultural land [37,58]. Land cover classes in Schleswig-Holstein are often initiated by the cultivation of silage maize for biogas plants that have been a widely discussed political issue in Germany.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Land cover distributions are driven by complex environmental, social and economic conditions that are focal points for sustainable land cover plans [56,57]. The distributions frequently change due to human activities that have been increasingly influenced by political plans during the last few centuries, for instance urbanization or intensively using agricultural land [37,58]. Land cover classes in Schleswig-Holstein are often initiated by the cultivation of silage maize for biogas plants that have been a widely discussed political issue in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneous conditions may lead to negative influences on the annual total GPP and NPP through affecting vegetation growth [65]. In addition to the distinctions of the annual total GPP and NPP owing to the locaton of the study area, nutrients availability which were imported during the process of fertilization, led to "pastures" showing a similar performance trend as forest (Table 1) [6,58]. However, the annual total GPP and the annual total NPP in the other land cover classes were different from the annual total GPP and the annual total NPP in pastures and forests.…”
Section: Discussionmentioning
confidence: 99%
“…Urbanization is encroaching on arable cereal farms and intensive vegetable growing horticultural areas in the Adelaide Plains to the north; a conservation green belt (the Hills face Zone) beyond which is a mixed farming belt to the east and the south east; and traditional wine producing areas to the south, east and north east (McLaren Vale, the Adelaide Hills and Barossa Valley respectively). Wadduwage et al (2017) identified three broad agricultural land-use types in this region: dryland agriculture (DL), land devoted to rearing livestock (LL) and horticultural areas (HL). The classes account for 0.3, 0.23 and 0.07 million ha respectively.…”
Section: Study Areamentioning
confidence: 99%
“…There are clear economic motivations for the rule of minimum subdivisions and the singular pattern of inheritance described above, since dividing up lands into smaller plots can cause land-fragmentation, thereby reducing cultivation output (see Teshome et al 2016;Wadduwage et al 2017;Xie and Lu 2017). We have already noted in the introduction and in relation to discourse 1, that in preparation of laws related to governing the land-water nexus in the north-central province, there has (historically) been a greater focus on irrigation development than on individual rights.…”
Section: Discourse 3: Inclusion Of Encroachers Based On Equitymentioning
confidence: 99%